Quasar – CIV forest cross-correlation with SDSS DR12. Issue 1 (7th July 2018) - Gontcho A Gontcho, Satya; Miralda-Escudé, Jordi; Font-Ribera, Andreu; Blomqvist, Michael; Busca, Nicolás G; Rich, James
ABSTRACT: We present a new determination of the large-scale clustering of the CIV forest (i.e. the absorption due to all CIV absorbers) using its cross-correlation with quasars in the Sloan Digital Sky Survey Data Release 12. We fit a linear bias model to the measured cross-correlation. We find that the transmission bias of the CIV forest, bFc, at a mean redshift of z = 2.3, obeys (1 + β _c)b_F c=-0.024 ± 0.003 . Here, β c is the linear redshift space distortion parameter of the CIV absorption, which can only be poorly determined at β c = 1.1 ± 0.6 from our data. The most accurately determined combination marginalized over β c is (1 + 0.44 β _c)b_F c=-0.0170 ± 0.0014 . The transmission bias is related to the bias of CIV absorbers and their host haloes, b τ c, through the effective mean optical depth of the CIV forest, which we estimate at τ _c(z) 0.01 from previous studies of the CIV equivalent width distribution. We then find 1 < b τ c < 1.7, with the large error arising from uncertainties in β c and τ _c . This CIV bias is lower than the DLA bias b DLA ≃ 2 measured previously from the cross-correlation of DLAs and the Ly α forest, indicating that most CIV absorbers are hosted by haloes of lower mass than DLAs. More accurate determinations of τ _c(z) and β c are necessary to check this conclusion.